Device-Based Enrichment of Knee Joint Synovial Cells to Drive MSC Chondrogenesis Without Prior Culture Expansion In Vitro: A Step Closer to 1-Stage Orthopaedic Procedures. Issue 1 (January 2022) - Altaie, Ala; Baboolal, Thomas G.; Wall, Owen; Pandit, Hemant; Jones, Elena; McGonagle, Dennis
Background: Synovial fluid (SF) mesenchymal stem cells (MSCs) are derived from the synovial membrane and have cartilage repair potential. Their current use in clinical practice is largely exploratory. As their numbers tend to be small, therapeutic procedures using MSCs typically require culture expansion. Previous reports indicate that the stem cell–mobilizing device (STEM device) intraoperatively increases SF-MSCs. Purpose: This study evaluated the chondrogenic potential of non–culture expanded synovium-mobilized MSCs and SF-microfragments obtained after enrichment using the STEM device and ascertained if device-mediated synovial membrane manipulation facilitated ongoing MSC release. Study Design: Controlled laboratory study. Methods: Two samples of aspiration fluid were collected intraoperatively before and after STEM device utilization from patients (n = 16) undergoing diagnostic or therapeutic knee arthroscopy. Human knee synovium (n = 5) was collected during total knee replacement, and a suspended culture was performed to assess the effect of the STEM device on ongoing MSC release. Colony forming unit–fibroblastic assays were used to determine the number of MSCs. Additionally, cytometric characterization of stromal and immune cells and chondrogenesis differentiation assay were performed without culture expansion. Filtered platelet concentrates were prepared using the HemaTrate system. Results: After STEM device use, a significant increase was evident in SF-MSCs ( P = .03) and synovial fluid–resident synovial tissue microfragments ( P = .03). In vitro–suspended synovium released significantly more MSCs following STEM device use than nonstimulated synovium ( P = .01). The STEM device–released total cellular fraction produced greater in vitro chondrogenesis with significantly more glycosaminoglycans (GAGs; P < .0001) when compared with non–STEM device synovial fluid material. Nonexpanded SF-MSCs and SF-microfragments combined with autologous filtered platelet concentrate produced significantly more GAGs than the complete chondrogenic media ( P < .0001). The STEM device–mobilized cells contained more M2 macrophage cells and fewer M1 cells. Conclusion: Non–culture expanded SF-MSCs and SF-microfragments had the potential to undergo chondrogenesis without culture expansion, which can be augmented using the STEM device with increased MSC release from manipulated synovium for several days. Although preliminary, these findings offer proof of concept toward manipulation of the knee joint environment to facilitate endogenous repair responses. Clinical Relevance: Although numbers were small, this study highlights 3 factors relevant to 1-stage joint repair using the STEM device: increased SF-MSCs and SF-microfragments and prolonged synovial release of MSCs. Joint repair strategies involving endogenous MSCs for cartilage repair without the need for culture expansion in a 1-stage procedure may be possible.